2018
DOI: 10.1111/jocd.12519
|View full text |Cite
|
Sign up to set email alerts
|

Safety and complications of absorbable threads made of poly‐L‐lactic acid and poly lactide/glycolide: Experience with 148 consecutive patients

Abstract: The procedure using sutures made of absorbable poly-L-lactic acid and poly lactide/glycolide is a relatively safe procedure without major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 21 publications
0
30
2
Order By: Relevance
“…Their results showed that dimple was the most common complication. However, dimple was the least postoperative complication in our study, showing the inconsistency of the results in two studies . Ogilvie et al (2017) reported mild complications for the surgery.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Their results showed that dimple was the most common complication. However, dimple was the least postoperative complication in our study, showing the inconsistency of the results in two studies . Ogilvie et al (2017) reported mild complications for the surgery.…”
Section: Discussioncontrasting
confidence: 66%
“…However, dimple was the least postoperative complication in our study, showing the inconsistency of the results in two studies. 23 However, considering the rate of complications, it can be stated that no serious complications were observed in either of these studies. 24 Savoia (2014) reported mild complications for the operation, namely ecchymosis, mild erythema, small hemorrhage, mild transitory esthesia, and mild postoperation tumefaction.…”
Section: Discussionmentioning
confidence: 76%
“…Kim et al used a unidirectional barbed thread and inserted it from the lower face to the temple area where the FBrSTA is located. Sarigul Guduk et al used a poly‐L‐lactic acid thread with cones, and the entry point was not made at the hairline but in the upward direction toward the temple area. Suh et al used bilateral cogged PDO threads, which were inserted near the skin of the nasolabial fold, and an additional entry point was made at the hairline.…”
Section: Discussionmentioning
confidence: 99%
“…However, facelift surgeons often operate on patients who previously had poorly performed facelifts with undesirable results 5 14 or on those who underwent multiple injectable therapies after the initial facelift, producing unnatural results, or on those who had noninvasive treatments with devices or threads in an effort to correct the recurrent laxity. 15 17 All of the abovementioned procedures render the revision facelift more difficult.…”
Section: Introductionmentioning
confidence: 99%